Tinjauan Yuridis Sertifikat Hak Tanggungan Yang di Terbitkan Melalui Sistem Elektronik Menurut Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional No. 5 Tahun 2020 Tentang Pelayanan Hak Tanggungan Terintegrasi Secara Elektronik - Gratia Ariefa (Universitas Harapan Medan, 2022)
The registration system for Electronic Mortgage Rights (HT-el) is intended to improve service, timeliness, speed, convenience and affordability in the context of public services, as well as to adjust legal developments, technology and community needs. type of . HT-el services that can be delivered through the HT-el System include registration of HT, transfer of HT, change of creditor name, deletion of HT and data correction. Electronic HT certificate that has executive power and can be proven as evidence of HT in court. The results show that in conventional HT registration, the legal provisions of UUHT, PP 24/1997 and PP 37/1998 require PPAT to send physical documents to the land office and thus require the Land Office to receive and keep the mortgage registration documents in the original. HT registration through HT-el, PPAT has the role of submitting the deed and complete documents of registration requirements or transfer of HT requested by the Creditor through the PPAT Partner Application at partner.atrbpn.go.id which is integrated with the HT-el System where the submission of documents is accompanied by a Statement Letter regarding accountability for the truth and validity of the data. Electronic Documents submitted. The HT-el certificate has executive powers as regulated in Article 14 of the HT Law and can be executed under Article 224 HIR. The HT-el service carried out by the Ministry of ATRIBPN is a form of Public Scope Electronic System Operation as regulated in UU ITE Jo. PP 7 I/2019. In addition, the ITE Law is the legal basis for HT-el certificates which are legal evidence of HT in the eyes of the law and can be used as evidence in court.